The Relationship betweenMoral Education by Parents and Moral Behavior of Early Children inJorongTanjuangPangka, West Pasaman District - Fitriana, Liza; Sunarti, Vevi (Universitas Negeri Padang, 2024)
This study is driven by the poor ethical conduct of young children in Jorong Tanjuang Pangka, West Pasaman Regency. This is allegedly due to moral education by parents. This study aims to: 1) describe moral education by parents; 2) describe the moral behavior of early childhood in Jorong Tanjuang Pangka, West Pasaman Regency; 3) examining the correlation between parental moral instruction and the ethical conduct of young children in Jorong Tanjuang Pangka, West Pasaman Regency. This form of investigation is correlational in nature, employing a quantitative methodology, with the objective of revealing associations. The population of this study were parents who had children aged 4-6 years in Jorong Tanjuang Pangka, West Pasaman Regency, totaling 76 people and 60% were sampled, namely 46 people using a purposive sampling technique. Data gathering methods employing a survey. Data interpretation methods utilize the proportion equation and the coefficient of correlation equation. The findings of the investigation indicate that: 1) moral education by parents is low; 2) the moral behavior of early childhood in Jorong Tanjuang Pangka, West Pasaman Regency, is classified as low; 3) there is a notable correlation between moral education by parents and the moral behavior of early childhood in Jorong Tanjuang Pangka, West Pasaman Regency.